(untitled) (Academia Science Repository, 2023)
This article studies the essence, importance, characteristics, organization and regulation of capital market and corporate securities operations. Moreover, organization and regulation of corporate securities operations in capital market in Uzbekistan are analyzed in detail. Scientific conclusions and recommendations are presented on organization and regulation of corporate securities operations in capital market in Uzbekistan.